MOLECULAR BASIS OF CANAVANINE SYNTHESIS IN ORGAN CULTURES OF LESSERTIA FRUTESCENS - Colling, J.; Jens Kossmann, J.; Makunga, N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Lesserita frutescens, formerly known as Sutherlandia frutescens, has a long-standing history of use as an ethnomedicinal plant for various ailments and diseases in the Western Cape (South Africa). Phytochemical analysis indicates the presence of a complex mixture of compounds including triterpenoid glycosides, flavonoids, amino acids and small amounts of saponins. L-canavanine, asparagine, GABA, L-arginine and pinitol are key components of many legumes including Lessertia. L-Canavanine is thought to largely contribute to the health promoting effects of this plant. In the Western Cape, this plant is reputed to be useful in retarding cancerous growths and is thus locally known as ’kankerbos’ (cancer-bush). The efficacy of Lessertia as a chemotherapeutic agent remains largely inconclusive. Even so, a biotechnological approach using organ cultures has been a useful tool to study the molecular basis of canavanine synthesis in our laboratories. Fifteen transgenic hairy root clones were generated through Agrobacterium transformation using hypocotyls explants and these established readily in both liquid and solid culture. However, four putative transformed clones exhibited typical hairy root characteristics. Transformation was examined via PCR amplification with a 600 bp fragment confirming presence of rol C as the transgene. Concomitant to this, a vigorous plantlet regeneration system using nodal explants with rooting occurring spontaneously has been developed. Metabolic profiling and molecular biological analysis of hairy root and in vitro shoot cultures has indicated that canavanine synthesis may be manipulated by adjusting components of the culture micro-environment.